2021
DOI: 10.1021/acs.chemrestox.0c00448
|View full text |Cite
|
Sign up to set email alerts
|

Post-Mortem Metabolomics: A Novel Approach in Clinical Biomarker Discovery and a Potential Tool in Death Investigations

Abstract: Metabolomics can be defined as the scientific field aiming at characterizing all low-weight molecules (so-called metabolites) in a biological system. At the time of death, the level and type of metabolites present will most likely reflect the events leading up to death.In this proof of concept study, we investigated the potential of post-mortem metabolomics by identifying post-mortem biomarkers, correlated these identified biomarkers with those reported in clinical metabolomics studies, and finally validated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Previously, only a few studies have investigated the associations between metabolome differences and postmortem interval (PMI) [2][3][4]. However, advances have been made recently in expanding the utility of untargeted metabolomics as a potential tool in death investigations, specifically in deaths related to pneumonia [5] and oxycodone intoxication [6]. In these studies, untargeted metabolomics using multivariate statistical modeling could classify specific causes of death, with high sensitivity and specificity, based on the metabolic fingerprint of postmortem blood samples [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, only a few studies have investigated the associations between metabolome differences and postmortem interval (PMI) [2][3][4]. However, advances have been made recently in expanding the utility of untargeted metabolomics as a potential tool in death investigations, specifically in deaths related to pneumonia [5] and oxycodone intoxication [6]. In these studies, untargeted metabolomics using multivariate statistical modeling could classify specific causes of death, with high sensitivity and specificity, based on the metabolic fingerprint of postmortem blood samples [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In general, OPLS-DA, Pearson correlation, and FDR q -values give the most valuable information when evaluating based on the number of prioritized metabolites found, that also have been reported in previous controlled studies ( Steuer et al, 2019 ). These feature selection methods have also been used in previous metabolomics studies ( Nielsen et al, 2016 ; Elmsjö et al, 2020 ; Jung et al, 2021 ), where meaningful results also were reported using these methods. Mass spectrometrory metabolome data analysis is complicated, since metabolites interact nonlinearly, and the data structures themselves are complex, especially when the study is retrospective and uncontrolled.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to MDMA, GHB is an endogenous compound, and the concept still needs further proof and verification for such more complicated cases. More recently, the principle was also applied by other groups to detect novel direct metabolites of valproate, as well as to examine whether data from post-mortem samples can be used to get insight into mechanism of death ( Mollerup et al, 2019 ; Elmsjö et al, 2020 ). Still, the method is yet in its infancy and needs further development to, e.g., tackle archived data produced over a longer period, as the shift of retention time (RT) and intensity is much larger in retrospective analysis compared to single or consecutive runs as is custom in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Elmsjö et al suggested post mortem metabolomics to be a useful tool in death investigations by comparing the post mortem metabolome in pneumonia cases with control cases. Amino acids, carnitines, lipids, nicotinamides, nucleotides, and steroids were found to significantly separating the groups (105). In metabolomics, the biostatistic methods used are commonly unsupervised principal component analysis (PCA) to provide an overview of the data and display systematic variation, in combination with supervised orthogonal partial least square (OPLS) models to identify metabolites/biomarkers contributing to group separation.…”
Section: Metabolomicsmentioning
confidence: 99%